SLOPE STABILITY ANALYSIS OF PT XYZâS TAILING QUARTZ SAND QUARRY USING FINITE ELEMENT METHOD - Wendy Andreani, Novia
Slope stability analysis is one of important parameters in mine planning or mining implementation. One of the slope stability analysis methods is numerical model using 2D Finite Element Method, which is carried out by modeling the vertical section of the most critical slope. The modeling includes insertion of geometry limit, material type, mesh discretization, and material properties which control the slope. The assumptions used are horizontal seismic loading factor of 0.01g and the condition of the groundwater table follows the slope contour with Hu value of 0.6. The simulation is carried out by RS2 software to obtain the Factor of Safety (FoS) value of the slope using critical Strength Reduction Factor (SRF) value approach. The minimum slope FoS criteria are based on the Decree of the Minister of Energy and Mineral Resources No. 1827 K/30/MEM/2018, which are static FoS ? 1.3 and dynamic FoS ? 1.1. From the simulation results, the initial slope dynamic FoS value is 0.74, which indicates that the slope is unstable. Thus, recommendations are needed to overcome the slope instability. There are two recommendations: (1) resloping the slope, which originally had a single slope angle of 45° to 25° or (2) resloping the slope, which originally had a single slope angle of 45° to 30° and providing retaining embankment at the foot of the slope. These two recommendations produce a dynamic FoS value of ? 1.1. Therefore, the slope recommendations can be implemented.